Squamous cell carcinoma in burn scars: report of three cases - Azmi, Siti Hanisah; Ahmad Affandi, Khairunisa; Abd. Fuaat, Azliana; Hamdan, Asmah Hanim (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2021)
Introduction: Squamous cell carcinoma (SCC) is a malignant tumour of epidermal keratinocytes. SCC may arise in chronically inflamed lesions such as burn scars and chronic ulcers. Here, we report three cases of SCC arising from pre-existing burn scars. Cases presentation: Case 1: A 63-year-old lady presented with a four-months duration of progressive skin tumour over right shoulder scar. She had burn injury over the right shoulder for more than 50 years. She underwent wide local excision of the mass and the histopathological examination (HPE) reported as well-differentiated SCC. Case 2: A 53-year-old gentleman presented with a one-year history of skin growth over left shin. He had burn injury over left lower limb since the age of 10. He underwent left above-knee amputation (AKA) and HPE reported as well-differentiated SCC. Case 3: A 31-year-old man presented with non-healing ulcers over bilateral ankles. He sustained burn injury over bilateral upper and lower limbs at the age of 11. He underwent right AKA and HPE reported as well differentiated SCC. Discussion: Malignant transformation from burn is usually slow. This type of SCC is aggressive and associated with poor prognosis. Conclusion: SCC can complicate long-standing burn scars; therefore, follow-up is recommended to look for malignant changes.